Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/mlr.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults With Hip Fractures Disadvantaged in Level 1 Trauma Centers?

Abstract: Older adults with hip fractures may be disadvantaged in L1TCs. Further research should aim to develop our understanding of this disparity to ensure that all patient groups benefit from the resources and expertise available within these hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have shown an association between a higher volume of hip fracture surgeries and delays, complications and death. 40,41 The studies suggest underprioritization of hip fracture over other surgeries at high-volume sites. 40,41 Hospital occupancy has also been associated with risk of in-hospital death after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown an association between a higher volume of hip fracture surgeries and delays, complications and death. 40,41 The studies suggest underprioritization of hip fracture over other surgeries at high-volume sites. 40,41 Hospital occupancy has also been associated with risk of in-hospital death after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The studies suggest underprioritization of hip fracture over other surgeries at high-volume sites. 40,41 Hospital occupancy has also been associated with risk of in-hospital death after hip fracture. 31 Future research should explore the association among teaching status, bed capacity, occupancy and volume to better our understanding of outcomes of hip fracture care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…79 Resource availability depends on whether the prioritization places hip fracture cases over other urgent trauma cases. 20,41,80 Where implemented, policies on access to surgery have been intended to address a lesser priority for hip fracture surgery and shortened time to surgery in some hospitals. 3 The presence of an institution's access and discharge policy depends on the calendar period when a patient underwent surgery, conceptualized here as treatment era.…”
Section: Mediating Factorsmentioning
confidence: 99%
“…Hospital type Trauma center designation increases hospital workload, and hip fracture patients may be given lower priority than patients needing more urgent care in trauma centers. 80…”
Section: Structurementioning
confidence: 99%
“…Some have argued that understanding the effects of policy change should guide reorganization of operating room resources 26 and prioritization in the presence of competing demand. 7,[27][28][29] In this paper, we offer 2 new estimates: the effect of possible changes in surgical timing policy in the same popula tion of patients, and the proportion of inhospital deaths attrib utable to surgical delays.…”
mentioning
confidence: 99%